DENTAL ANXIETY AND THE NEED FOR COMPLEX ORAL REHABILITATION IN PATIENTS WITH DYSFUNCTION SYNDROME OF STOMATOGNATHIC SYSTEM AND PSYCHIATRICAL DISEASE - Lucian Ștefan Burlea; Ovidiu Stamatin; Ana Maria Ciubara; Bogdan Petru Bulancea; Iulian Costin Lupu; Elena Roxana Almasan; Tudor Hamburda; Liana Aminov; Laura Elisabeta Checheriță (Romanian Society of Oral Rehabilitation, 2021)
Dental anxiety and dysfunctional syndrome of the stomatognathic system are common in dental pathology. When the dysfunctional syndrome of the stomatognathic system interferes with the psychiatric pathology, there are cases with a high index of complexity that can be treated only by interdisciplinary approach dentistry-psychiatry. In this context, the long duration of dental treatment requires professionalism and good clinical management of the case. These complex cases, represents the major indication for the case management under anesthesia. In addition, the attitude of the dentist, his good communication with the patient as well as the staging of the treatment plan are important factors in prosthetic recovery, endodontic and periodontal treatments and are pillars of the complex oral rehabilitation of the case and of avoiding complications. In conclusion, case management under anesthesia/or special anesthesia remains a therapeutic solution of last resort in patients suffering from dysfunction syndrome of stomatognathic system in the context of dental anxiety or dental phobia and psychic affectation.